Preferensi siswa terhadap perilaku konselor dengan minatnya pada program bimbingan dan konseling - M Fatchurahman; Bulkani Bulkani (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2018)
This study aimed to describe (1) students' preferences on counselor behavior, (2)student interest in guidance and counseling program, and (2) relation between student preference to counselor behavior and interest to counseling and guidance program. The research was conducted in Junior High School (SMP) in Palangka Raya City with a population of 843 students. The sample of this study is 84 students taken proportional random sampling. The result of this research are (1) students' preference toward counselor behavior is positive, (2) student's interest toward guidance and counseling program tends to be positive, and (3) there is a positive correlation between student preference toward counselor behavior and interest to guidance and counseling program.